On-line orientation of bromine isotopes - Barham, C; Alghamdi, S; Bhagwat, A; Booth, M; Grant, I; Lindroos, M; Rikovska, J; Singleton, B; Stone, N; Walker, P (Kluwer Academic Publishers, 1992)
Assignments for the principal Nilsson configuration in light β+-decaying bromine isotopes were proposed in a contribution to the OLNO-1 conference. These assignments were made on the basis of magnetic moments derived from the temperature dependence of anisotropies in daughter Se isotopes observed in the DOLIS-COLD facility at Daresbury. Anisotropy measurements have since been extended to a lower base temperature in74 mBr and72 gBr decay, leading to more stringent limits on the ground state moment of72Br. The proposed π[312]3/2 configuration for75Br has also now been confirmed by a measurement of the sign of its magnetic moment. This was done by observing the β-asymmetry in75Br decay using high purity Si detectors mounted within the dilution refrigerator. © 1992 J.C. Baltzer A.G., Scientific Publishing Company.